2016
DOI: 10.3389/fendo.2016.00090
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Adipose Tissue: A New Player in Cancer Metastasis to Bone

Abstract: The bone marrow is a favored site for a number of cancers, including the hematological malignancy multiple myeloma, and metastasis of breast and prostate cancer. This specialized microenvironment is highly supportive, not only for tumor growth and survival but also for the development of an associated destructive cancer-induced bone disease. The interactions between tumor cells, osteoclasts and osteoblasts are well documented. By contrast, despite occupying a significant proportion of the bone marrow, the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 67 publications
1
54
0
Order By: Relevance
“…A mutually incompatible relationship arises between adipose components of the BM and bone-forming components, as osteoblastogenesis and the factors that support it often inhibit adipogenesis, and vice versa. This is consistent with the inhibition of bone formation often performed by BMAT [21]. This may be due to direct effects of these cells on each other or could be due to lineage competition that results from the fact that both osteoblasts and adipocytes derive from the same precursor cell.…”
Section: Bone Marrow Adipose Tissuesupporting
confidence: 87%
See 3 more Smart Citations
“…A mutually incompatible relationship arises between adipose components of the BM and bone-forming components, as osteoblastogenesis and the factors that support it often inhibit adipogenesis, and vice versa. This is consistent with the inhibition of bone formation often performed by BMAT [21]. This may be due to direct effects of these cells on each other or could be due to lineage competition that results from the fact that both osteoblasts and adipocytes derive from the same precursor cell.…”
Section: Bone Marrow Adipose Tissuesupporting
confidence: 87%
“…A key regulator of skeletal biology, hematopoiesis, and metabolic activity, BMAT is also involved in endocrine functions and the secretion of fatty acids, chemokines, and adipokines [21]. BMAT volume increases with age and occupies a significant portion of the BM, as well as composing over 10% of the average person's total adipose tissue mass [21].…”
Section: Bone Marrow Adipose Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, they secrete a large panel of bioactive molecules, named adipokines, including hormones, growth factors, chemokines and pro-inflammatory molecules, whose balance is perturbed in obesity (123,124). Due to the distribution of adipose tissue (AT), many cancer cells will come into contact with adipocytes during local invasion (for example in breast, colon and prostate cancers, as well as melanoma) but also distant dissemination (to the omental fat for gastric and ovarian cancer, but also to the bone marrow) (125,126). Using a coculture system, we have demonstrated that adipocytes cultivated with cancer cells display a modified phenotype, with decreased lipid content and downregulation of adipocyte markers.…”
Section: Adipocytes As Key Players In the Tumor Microenvironmentmentioning
confidence: 99%